Push-Out Bond Strength and Dentinal Penetration of a Novel Herbal-Based Pulp Capping Agent: An In vitro Study - Hamdy, Mai; Elgendi, Huda; Sharaan, Marwa (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: Pulp capping agents should have proper sealing effect to enhance dental pulp tissue healing. Aim: The purpose of this study was to compare the effectiveness of grape seed extract (GSE) and Mineral trioxide aggregate (MTA) to penetrate to dentin and their push-out bond strength at two time intervals (1 and 3 months) when used as pulp capping agents either singly or combined to each other. Materials and Methods: This study was conducted on 120 human single-rooted anterior teeth. Sixty dentin discs were randomly divided into three groups (n=20) based on the material used; MTA, GSE, and a combination of MTA and GSE. A universal testing machine was used to determine the push-out bond strength for one and three months. At the same time intervals, extra 60 teeth with the same groups were utilized to quantify the degree of capping material penetration within the dentinal tubules using scanning electron microscopy (SEM). ANOVA with multiple comparison Post hoc test was used to evaluate the data where the p value was < 0.05. Results: MTA had the highest push-out bond strength and penetration depth measurement into dentinal tubules at one month, followed by MTA combined with GSE, while GSE had the lowest push-out bond strength and penetration depth measurement. Nevertheless, GSE had the greatest values in both tests at 3 months, followed by MTA, while MTA coupled with GSE had the lowest value in both tests. Conclusion: Push out bond strength and dentinal penetration depth were improved with time except for the MTA group testing its dentinal penetration depth. GSE shows good push out bond strength and dentinal penetration depth.